Minimum acceptable diet and associated factors among infants and young children aged 6–23 months in Amhara region, Central Ethiopia: community-based cross-sectional study - Lemma Getacher; Abebaw Molla; Bezie Kebede; Alemayehu Sayih; Mikyas Arega; Agegnehu Bante (BMJ Open)
Objective The main objective of this study was to assess the prevalence of a minimum acceptable diet (MAD) and associated factors.Design Community-based cross-sectional studySetting Debre Berhan Town, Ethiopia.Participants An aggregate of 531 infants and young children mother/caregiver pairs participated in this study. A one-stage cluster sampling method was used to select study participants and clusters were selected using a lottery method. Descriptive statistics were calculated for all study variables. Statistical analysis was performed on data to determine which variables are associated with MAD and the results of the adjusted OR with 95% CI. P value of <0.05 considered statistically significant.Primary outcome Prevalence of MAD and associated factorsResults The overall prevalence of MAD was 31.6% (95% CI: 27.7 to 35.2). Having mother attending secondary (adjusted OR, AOR=4.9, 95% CI: 1.3 to 18.9) and college education (AOR=6.4, 95% CI: 1.5 to 26.6), paternal primary education (AOR=1.3, 95% CI: 1.5 to 2.4), grouped in the aged group of 12–17 months (AOR=1.8, 95% CI: (1.0 to 3.4) and 18–23 months (AOR=2.2, 95% CI: 1.2 to 3.9), having four antenatal care (ANC) visits (AOR=2.0, 95% CI: 1.0 to 3.9), utilising growth monitoring (AOR=1.8, 95% CI: 1.1 to 2.9), no history of illness 2 weeks before the survey (AOR=2.9, 95% CI: 1.5 to 6.0) and living in the household with home garden (AOR=2.5, 95% CI: 1.5 to 4.3) were positively associated with increase the odds of MAD.Conclusion Generally, the result of this study showed that the prevalence of minimum acceptable was very low. Parent educational status, ANC visits, infant and young child feeding advice, child growth monitoring practice, age of a child, a child has no history of illness 2 weeks before the survey, and home gardening practice were the predictors of MAD. Therefore, comprehensive intervention strategies suitable to the local context are required to improve the provision of MAD.